THE PROBLEM OF FUNCTIONAL AND PRAGMATIC CHARACTERISTRICS OF BASIC COMPONENTS OF COMMUNICATION IN DIFFERENT CONTEXTS (Web of Teachers: Inderscience Research, 2024)
The given article is devoted to the problem of functional and pragmatic characteristrics of basic components of communication in different contexts. In modern research, special attention is paid to the functional and pragmatic characteristics of the main components of communication, such as linguistic signs, participants in communication, as well as their interaction in various contexts. Understanding these characteristics allows us not only to gain a deeper understanding of communication processes, but also to develop more effective communication models in a wide variety of situations.